Developing and Promoting a Health Package Tour in Da Nang at Love Vietnam Tourism and Service Company Limited - Le, Thi Le Quyen (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management